Dislexia: inconsistências e incongruências sob o olhar da literatura específica - Felix, Tatiana Emanuela Rangel (2011)
The dyslexia entity is a well commented issue, and at the same time full of controversies, among the health professionals who deal with children with reading and learning difficulties. Speech therapists and educational psychologists have different points of view while facing the dyslexia theme and students who cannot read and learn the same way others do. For some professionals, there is no pathology, but for others, the dyslexic children are prevented, by the illness, to learn like the others do. Objective: To investigate the inconsistencies and incongruities in the specific literature about the concept/definition, evaluation/diagnosis and the treatment involving Speech Therapy and Educational Psychology private clinics while dealing with dyslexia. Method: Research and literature review about dyslexia using articles published from 2001 to 2011 in Brazilian journals indexed in the databases LILACS and SciELO. The keywords used were dyslexia, learning, reading and writing disorder. The final corpus was composed by 44 articles 30 written by speech therapists and 14 by educational psychologists. Results: 25 out of the 30 articles written by speech therapists presented the concept of the dyslexia, 30 offered the diagnosis and only 12 mentioned the treatment. 11 out of the 14 articles written by educational psychologists mentioned the concept of the dyslexia, 12 the diagnosis and 2 presented the treatment. Conclusion: It is suggested that such a scenario is due to the hegemony of a line of argument that tends to overwhelm the voices of dissent and that listens to these voices could lead to important changes in both areas, in order to clarify and tools and teachers in relation to dyslexia, undoing, effectively, the inconsistencies and discrepancies identified